A Survey of Emerging Trends on Medical Image Enhancement Techniques - Panse, Vijay; Gupta, Rajendra (International Journal of Computer Sciences and Engineering, 2025)
During image acquisition, inadequate brightness may cause poor contrast and noise in many images like medical, satellite images. So it is required to improve the contrast and eliminate the noise to increase image quality. So image enhancement is required in medical image to improvement in quality. In this paper, we describe the overview of medical image enhancement techniques, classification of image enhancement techniques, researches done in the field of medical image enhancement, shortcoming comes after reviews, Parameter used to check the quality of enhanced images, and general needs required in this field of active research.